Preoperative identification of low-risk patients for major complications after acute hip fracture surgery in geriatric patients: an observational cohort study - Eveline de Haan; Anna de Ronde; Louis de Jong; Veronique. A. J. I. M. van Rijckevorsel; DHFR; Gert R. Roukema (BMC Musculoskeletal Disorders, 2025)
Abstract Introduction Not all older patients with hip fractures exhibit frailty and a high risk of complications. Identifying low-risk patients allows more cost-effective treatment strategies. This study aims to identify the patients’ characteristics associated with a reduced risk of major complications following acute hip fracture surgery in elderly patients. Patients and methods A prospective hip fracture database was used to obtain data for this observational cohort study. Complications during hospitalization were categorized as major and minor. Both univariable and multivariable analyses were conducted to determine factors significantly correlated with a hospital stay without major complications in patients of 65 years and older. Results In total, 2304 patients were analyzed, of whom 771 (33.5%) had one or more major complications. The following characteristics were associated with an uncomplicated hospital stay after hip fracture surgery; age lower than 75 years, female gender, ASA 1 and 2, no history of atrial fibrillation, nor chronic obstructive pulmonary disease, nor dementia, nor Parkinson, nor myocardial infarction, The Katz Index of Independence in activities of daily living (Katz-ADL) of 6, an albumin above 35 g/L and no use of a walking aid. Patients without major complications had significantly shorter hospital stays and lower rates of 30-day and 1-year mortality. Conclusion This study identifies specific characteristics that can help select patients at low risk for major complications after hip fracture surgery. Patients with a low risk of complications may probably not require extensive geriatric care, enabling more efficient allocation of healthcare resources and contributing to cost reduction.